2021
DOI: 10.1017/s0013091521000304
|View full text |Cite
|
Sign up to set email alerts
|

Algebras with representable representations

Abstract: Just like group actions are represented by group automorphisms, Lie algebra actions are represented by derivations: up to isomorphism, a split extension of a Lie algebra $B$ by a Lie algebra $X$ corresponds to a Lie algebra morphism $B\to {\mathit {Der}}(X)$ from $B$ to the Lie algebra ${\mathit {Der}}(X)$ of derivations on $X$ . In this article,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…For instance, Remark 7.9 indicates a close relationship between cosmash associativity and algebraic coherence, which may well be valid outside the context of varieties of algebras over a field. A similar question makes sense for action accessibility [4], which is known to be equivalent to algebraic coherence in our present context [9]. The fact that there are no non-abelian varieties over a field which are both cosmash associative and locally algebraically cartesian closed [12]-combine the start of the Introduction, Example 7.5 and Example 8.3may also be an instance of a more general result.…”
Section: Final Remarksmentioning
confidence: 77%
See 1 more Smart Citation
“…For instance, Remark 7.9 indicates a close relationship between cosmash associativity and algebraic coherence, which may well be valid outside the context of varieties of algebras over a field. A similar question makes sense for action accessibility [4], which is known to be equivalent to algebraic coherence in our present context [9]. The fact that there are no non-abelian varieties over a field which are both cosmash associative and locally algebraically cartesian closed [12]-combine the start of the Introduction, Example 7.5 and Example 8.3may also be an instance of a more general result.…”
Section: Final Remarksmentioning
confidence: 77%
“…In previous work, characterisations of the variety Lie K of Lie algebras over an infinite field K (such that charpKq ‰ 2) as a subvariety of Alg K were obtained, in essentially two different ways: in [10,11], it is shown that Lie K is the only non-abelian locally algebraically cartesian closed [12] subvariety of Alg K ; and in [9], the variety Lie K is shown to be the only subvariety of Alg K whose actions are representable [3]. So we have two independent categorical descriptions of the variety Lie K , and thus of the Jacobi identity (however, only for anticommutative algebras).…”
mentioning
confidence: 99%
“…Like the characterisations of the variety of Lie algebras in [12,14], our work uses computer algebra, though in a significantly different way. Comparing the thus obtained characterisations does, however, lead to an intriguing open problem.…”
Section: Theorem Suppose That 𝔐 Is a Non-trivial Variety Of Non-assoc...mentioning
confidence: 99%
“…However, the notion of action representable category has proven to be quite restrictive. For instance, in [8] the authors proved that, if a variety of non-associative algebras (over a field with ) is action representable, then .…”
Section: Preliminariesmentioning
confidence: 99%